Monitoring for freshwater mussel presence in rivers using environmental DNA. Issue 3 (28th October 2020) - Preece, Ellen P.; Bryan, Michael; Mapes, Samantha M.; Wademan, Cara; Dorazio, Robert
Abstract: In 2013, the U.S. Environmental Protection Agency (USEPA) updated its national recommended water quality criteria for the protection of aquatic life from the toxic effects of ammonia in freshwaters. From its updated national dataset, USEPA determined freshwater mussels in the family Unionidae were the most sensitive taxa to ammonia. Thus, it has become necessary to determine whether freshwater mussels exist in waterbodies near discharge locations from Publically Owned Treatment Works (POTWs), to ensure that POTWs are regulated appropriately with regard to ammonia levels in their treated effluent. However, because mussels are notoriously difficult to detect using traditional survey methodologies, most POTWs have not determined whether freshwater mussels exist in their receiving waters. Environmental DNA (eDNA) presents a promising methodology to survey for freshwater mussels in POTW receiving waters. We developed and validated a quantitative polymerase chain reaction (qPCR) assay for the three freshwater mussel taxa that are currently known to exist in California's Central Valley. We then placed a cage with 20 Gonidea angulata into a riverine environment and collected water samples at evenly spaced downstream intervals to determine how habitat type and distance from the caged mussels affected eDNA detection. Using two‐stage occupancy modeling, we determined higher detection probabilities occur in riffle habitats compared to pool or run habitats. We also found surface samples work well for collecting freshwater mussel eDNA in riffle habitats, but are less likely to capture mussel eDNA in pools or runs. The maximum downstream distance at which the eDNA from the 20 placed G. angulata mussels was detected was 8 km. Our study demonstrates that eDNA is a reliable tool for determining freshwater mussel presence in riverine systems, but that sampling should consider habitat type, distance between sampling locations, and time of year for the most effective results. Abstract : We developed and validated a quantitative polymerase chain reaction (qPCR) assay for the three freshwater mussel taxa that are currently known to exist in California's Central Valley. We then placed a cage with 20 Gonidea angulata into a riverine environment and collected water samples at evenly spaced downstream intervals to determine how habitat type and distance from the caged mussels affected eDNA detection. Using occupancy modeling, we determined higher detection probabilities occur in riffle habitats compared to pool or run habitats.